Comparative genomics of the Liberibacter genus reveals widespread diversity in genomic content and positive selection history - Batarseh, Tiffany N.; Batarseh, Sarah N.; Morales-Cruz, Abraham; Gaut, Brandon S. (Frontiers in Microbiology, 2023)
Candidatus Liberibacter' is a group of bacterial species that are obligate intracellular plant pathogens responsible for Huanglongbing disease of citrus trees and Zebra Chip in potatoes. Here, we examined the extent of intra-and interspecific genetic diversity across the genus using comparative genomics. Our approach examined a wide set of Liberibacter genome sequences including five pathogenic species and one species not known to cause disease. By performing comparative genomics analyses, we seek to understand the evolutionary history of this genus and identify genes or genome regions that may affect pathogenicity. With a set of 52 genomes, we performed comparative genomics, measured genome rearrangement, and completed statistical tests of positive selection. We explored markers of genetic diversity across the genus, such as average nucleotide identity across the whole genome. These analyses revealed the highest intraspecific diversity amongst the 'Ca. Liberibacter solanacearum' species, which also has the largest plant host range. We identified the sets of core and accessory gene across the genus and within each species and measured the ratio of nonsynonymous to synonymous mutations (dN/dS) across genes. We identified ten genes with evidence of a history of positive selection in the Liberibacter genus, including genes in the Tad complex, which have been previously implicated as being highly divergent in the 'Ca. L. capsica' species based on high values of dN.